Dynamic mechanical properties of natural fiber reinforced hybrid polymer composites: a review - Haris, Nur Izzah Nabilah; Hassan, Mohamad Zaki; Ilyas, R. A.; Suhot, Mohamed Azlan; Sapuan, S. M.; Dolah, Rozzeta; Mohammad, Roslina; M. Asyraf, M. R. (Elsevier Editora, 2022)
The concerning waste management issue of natural fibers and the downsides of synthetic fibers have governed natural fibers' utilization as reinforcements in composites. Incorporating a single type of reinforcing fiber does not inevitably produce composites that meet exceptional quality standards, particularly in dynamic mechanical properties. Various studies have demonstrated excellent properties of natural fiber reinforced hybrid composites. Accordingly, this paper aims to review research related to natural fiber reinforced hybrid composites that emphasize the dynamic mechanical properties. A summary for each type of hybrid composites, including thermoset and thermoplastic polymers, biopolymers, nanocomposites, and bionanocomposites was provided. The variables of relevance in this overview are the loss modulus, storage modulus, damping factor, and glass transition temperature. Overall, the reviewed works revealed that lignocellulosic fibers are extensively used to reinforce composites. Nearly all hybridization of multiple reinforcing fibers had synergistic influences on the hybrid composites' dynamic mechanical properties. However, there are several cases whereby the addition of hybrid reinforcing particles leads to a detrimental effect on the composites’ quality. There is a limitless possibility for further improvements of natural fiber reinforced hybrid composites.